Association Between the Use of Oral Contraceptives and Patient‐Reported Outcomes in an Early Arthritis Cohort. Issue 3 (March 2016) - Albrecht, Katinka; Callhoff, Johanna; Buttgereit, Frank; Straub, Rainer H.; Westhoff, Gisela; Zink, Angela
Abstract : Objective: To evaluate the association between exposure to oral contraceptives (OCs) and clinical outcomes in an early arthritis cohort. Methods: Female patients with early inflammatory arthritis, ages 18–60 years, who were enrolled in an early arthritis cohort and had no exposure to hormone replacement were studied (n = 273). Associations between OC exposure (current/past/never) and disease activity, treatment, and patient‐reported outcomes, including the Rheumatoid Arthritis Impact of Disease Score (RAID), the Rheumatoid Arthritis Disease Activity Index (RADAI), the Profile of Mood and Discomfort (PROFAD), and the Hannover Functional Assessment (FFbH), were studied over 2 years. Linear mixed models adjusted for age, body mass index, parity, smoking, and education were used. Results: Eighteen percent of patients had never used OCs, 63% had used OCs in the past, and 19% currently used OCs. After adjustment, the current/past OC use was associated with better RAID, PROFAD, RADAI, and FFbH scores at 12 months ( P < 0.05 for all) compared to never use. Longitudinally over 2 years, the mean RAID scores were significantly better in women with current/past OC use ( P < 0.001). Actual inflammatory markers were not associated with OC use. Glucocorticoids were used by a higher percentage of OC never users than by current/past users ( P = 0.08), especially in patients with impaired function (FFbH <70: odds ratio 4.2 [95% confidence interval 1.6–11]). Conclusion: For past as well as current use, OCs seem to moderate patient‐reported outcomes in inflammatory arthritis. Protective effects may be induced via central nervous pathways rather than through the suppression of peripheral inflammation.